The Perceptions of a Farming Community in the Limpopo Province on HIV/AIDS - Klaas , Ntombifikile Elizabeth; Peu, Mmapheko Doriccah; Netangaheni, Thinavhuyo Robert (Asian Journal of Agriculture and Rural Development, 2014)
The HIV/AIDS pandemic has evoked a wide range of reactions from individuals, communities, and even nations. These reactions range from sympathy and caring to silence, denial, fear and anger. Little is known about the farming community’s views in Africa, and South Africa in particular. It is therefore crucial to understand these views in order to mitigate the spread of HIV/AIDS. An explorative and descriptive research design was applied. Purposive and convenience sampling was used to select participants with whom one-on-one semi- structured interviews were conducted between October and November 2012 in the Levubu farming community in the Limpopo Province. Data was collected until data saturation was reached and no new information was obtained. Data saturation was reached after interviewing fifteen participants and the author interviewed five more participants after data saturation. Tesch’s data analysis method was used. Four categories were identified during data analysis: emotions linked to HIV/AIDS, individual characteristics and experiences, behavior-specific cognition and affect and healthcare needs. Training on HIV/AIDS is crucial, as the study revealed that despite the ongoing HIV/AIDS awareness campaigns in South Africa, some segments of the population are not getting the message, specifically the farming community.